Modeling storm surge for the south central coast of Vietnam :Master thesis Major Coastal Engineering and Management: Code 60-58-02-03 - Ninh, Duy Quỳnh (Trường Đại học Thủy Lợi, 2020)
The main objective of this research is to setup a model to simulate storm surges along the southern coast of the central provinces and to investigate different factors that may influernce the accuracy of storm surge computation.